Response to the letter to the editor: different effect on improvement of renal injury in urinary albumin-creatinine ratio at different follow-up time and metabolic surgery - Billeter, Adrian; Scheurlen, Katharina; Probst, Pascal; Müller, Beat P. (Surgery for obesity and related diseases, 2020)
We have read with great interest the letter to the editor by Wang et al. [1]. They - analyzed the effect of time on the improvement of nephropathy in patients with type - 2 diabetes after metabolic surgery. They found that after 6 to 12 months, metabolic - surgery did not significantly improve nephropathy, yet there were significant improvements - of diabetic nephropathy after 12 to 24 months. Additionally, they found after >60 - months, that the effects of metabolic surgery are lost again. Despite stating that - they analyzed the effects of different types of metabolic surgery, they did not provide - data on the effects of different types of metabolic operations in their letter to - the editor.
Gesehen am 11.05.2020